Hubungan Antara Pengetahuan Tentang Pencegahan Asma Dengan Kejadian Kekambuhan Pada Penderita Asma Di Wilayah Kerja Puskesmas Ngoresan Surakarta - Hidayati, Putri; , Hj. Irdawati, S.Kep., Ns, M.Si.Med; , Dian Nur Wulanningrum S.Kep, Ns (2015)
Asma is a common chronic disorder of pulmonary that involves recurrence attacks of wheezing. According to the WHO prevalence of asthma is likely to increase and very high. The lack of knowledge in society about asthma and effort to do prevention asthma attack is less so the consequence is patients get recurrence. On average patients had a recurrence more than three times in a month and knowledge about asthma is still low. The purpose of this study was to determine the correlation between knowledge about prevention of asthma with recurrence in patients with asthma in Ngoresan public health service of Surakarta. The study was a descriptive correlative. Total population who experience reccurent asthma relapse was 49 patients and all of them taken a sample with a total sampling technique. The variables used in this study is knowledge as independent variables and recurrence of asthma as the dependent variable. The research instrument was the questionnaire. Data analysis techniques used by the analysis of Chi-Square. The results showed 16 respondents (33%) had less knowledge, 19 respondents (39%) had moderate knowledge, and 14 respondents (28%) had good knowledge. Judging from the relatively resurrence asthma often have 23 respondents (47%), sometimes as many as 18 respondents (37%), dan rarely 8 respondents (16%). The conclusion is there is a significant relationship between knowledge prevention of asthma with recurrence in patients with asthma in Ngoresan Public Health Service of Surakarta.